2018
DOI: 10.1007/s12013-018-0854-5
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of SG2NA Variants and their Interaction with DJ-1 and Calmodulin in vitro

Abstract: SG2NA was first discovered as nuclear autoantigen in lung and bladder cancer patient. It was named SG2NA as its expression increases during S to G2 phase of cell cycle. SG2NA/Striatin3 was classified as a member of Striatin family along with Straitin and Zinedin due to its structural and functional relatedness. At the molecular level, SG2NA is characterized by the presence of multiple protein-protein interaction domains viz., a caveolin binding motif, a coiled coil structure, Ca-calmodulin binding domain and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Members of the striatin family feature multiple protein-binding domains, such as a caveolin-binding motif, a coiled-coil structure, a calmodulin-binding site, and a WD-repeat domain. These domains can mediate the dimerization of members of the striatin family and their interaction with a series of proteins [9]. The STRN-ALK fusion gene, a new driver gene, has been found in multiple cancers, including thyroid cancer [10], non-small-cell lung cancer (NSCLC) [11], colorectal cancer [12], and renal carcinoma [13].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the striatin family feature multiple protein-binding domains, such as a caveolin-binding motif, a coiled-coil structure, a calmodulin-binding site, and a WD-repeat domain. These domains can mediate the dimerization of members of the striatin family and their interaction with a series of proteins [9]. The STRN-ALK fusion gene, a new driver gene, has been found in multiple cancers, including thyroid cancer [10], non-small-cell lung cancer (NSCLC) [11], colorectal cancer [12], and renal carcinoma [13].…”
Section: Introductionmentioning
confidence: 99%
“…These three proteins manifest in a conservative manner due to their presence both in fungi and higher eukaryotes (5). Numerous studies have reported that the STRN proteins are expressed in various organs such as the central nervous system (6), lung, kidney and testis (7). However, the exact expression pattern differs, which indicates that the STRN family of proteins possess abundant but differential functions at the organ level or cellular level (8).…”
Section: Introductionmentioning
confidence: 99%